THE REDUCTION OF CRIMINAL MINORITY (REMUNOM, 2024)
Criminal minority is a very controversial topic and with opinions that differ about its reduction, the protection of young offenders and the socio-educational process. It is a work that exposes themes that are encompassed within the main theme and that are very helpful for the study of juvenile offenders, aiming to be careful in the elaboration of punishments and/or in the decision to send them to detention centers that do not always rely on socio-educational projects to prevent the individual's recidivism. The objective of this work is to analyze the relationship between the age of criminal responsibility and the reduction of crime and violence. The methodology used consists of applied research, to acquire knowledge through studies to solve this problem, using specialized bibliographies on aspects of the rights of children and adolescents in Brazil, and for research the documentary bibliographic method will be used. At the end of this study, it is expected to understand how the reduction of criminal minority may or may not influence the entry of minors into the world of crime. The current criminal policy in Brazil has a repressive character and, therefore, is centered on the police, judicial and penitentiary systems. However, crime rates continue to rise, indicating that repressive criminal policies do not have the desired effects on the State and society. This indicates the need for changes in current criminal justice policies, especially in the measures adopted when the minor is under State custody. Undoubtedly, there is a need for more criminal prevention policies and public policies that guarantee the access of children and adolescents to their rights, thus curbing their entry into the world of crime.